PENGARUH PENGELOLAAN KEARSIPAN TERHADAP EFISIENSI KERJA KARYAWAN PADA PT. BPR PRISMA DANA MANADO - KAJUAL, ELENSYA; Areros, William A.; Asaloei, Sandra Ingrid (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
This research is motivated by the problems found in Bank Prekreditan Rakyat (BPR)office of Prisma Dana Manado, which is in the management of archive that is not veryproductive using work time so that the work quickly accumulate and the limited of humanresources. The purpose of this study is to find out how much influence of archivalmanagement to the work efficiency of employees at PT. BPR Prisma Dana Manado. And theconstraints faced are the maintenance of records that there are still records stacked in thecabinet so that the archive becomes easily damaged and also difficult to recover when neededat all times. This can certainly hamper office work. Therefore, there is a need for good andorganized archive management so that it is easier for employees to reinvent the archivequickly. Arrangement arrangement is one of the aspects that must be applied at the office tosupport the achievement of the goal of increasing productivity and efficiency of office work. Inthis research, the method used is descriptive quantitative research method by spreadingquestionnaire 50 respondents who become sample in this research. The data were collected byquestionnaires that have been tested for their validity and reliability. And our data analysis isdescriptive and inferential statistic, consisting of simple correlation coefficient and regressiondone by using program SPSS for windows version 24.0. The results showed that there is asignificant influence between archival management on work efficiency. From these results aredone and followed by analyzing the data obtained, then there is a significant influencebetween the influence of archival management on employee work efficiency at PT.BPRPrisma Dana Manado and this means the work hypothesis or alternative hypothesis accepted.this means there is a positive influence between the management of archives to the workefficiency of employees with a level of influence of 21.3%. for it suggested more increaseagain the existence of filing system and work efficiency.Keywords: Archives management, work efficiency.